2012
DOI: 10.5586/asbp.2012.031
|View full text |Cite
|
Sign up to set email alerts
|

Wild food plant use in 21st century Europe: the disappearance of old traditions and the search for new cuisines involving wild edibles

Abstract: IntroductionIn several countries and regions of Europe ethnobotanical studies and reviews give us a picture of traditionally used wild food plants (e.g. Poland [1][2][3][4][5][6][7][8], Spain [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], Portugal [26,27], Italy [28][29][30][31][32][33][34][35][36][37], Greece [38,39], France [40], , the whole Mediterranean area [42][43][44], Austria [45][46][47], Slovakia [48] and the Nordic countries [49,50]).Plant use patterns are usually not stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
230
1
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 337 publications
(271 citation statements)
references
References 44 publications
10
230
1
14
Order By: Relevance
“…Indeed, a recent European study revealed that migrants of the first generation, but not the following generations, showed some differences in using urban greenspaces compared to other people [36]. Future research to access a more diverse selection of urban foragers is thus needed, for Berlin and other European cities [30]. This is especially relevant in Germany following the European migrant crisis, which peaked in 2015, when 1.1 million people immigrated to the country [65].…”
Section: Who? Urban Foragersmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a recent European study revealed that migrants of the first generation, but not the following generations, showed some differences in using urban greenspaces compared to other people [36]. Future research to access a more diverse selection of urban foragers is thus needed, for Berlin and other European cities [30]. This is especially relevant in Germany following the European migrant crisis, which peaked in 2015, when 1.1 million people immigrated to the country [65].…”
Section: Who? Urban Foragersmentioning
confidence: 99%
“…People have relied on wild resources during war and times of crisis [27,28,30] including in Germany [67], sometimes leading them to be stigmatized as foods of famine and therefore later discontinued [68]. However, while some wild resource gathering fades, other resources with a higher cultural appreciation value continue to be gathered [31].…”
Section: Who? Urban Foragersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Iberian peninsula and Italy, dishes incorporating T. communis, A. acutifolius, A. ampeloprasum, N. officinale, M. fontana, B. officinalis, M. sylvestris, P. rhoeas, S. hispanicus, Rumex crispus L., and Urtica dioica L. (Fig. 1) can be found in some luxury restaurants (Bicho, 2015;Łuczaj et al, 2012). -Implementation of alternatives to wild-harvesting practices: Wild harvesting may represent a source of income for rural communities.…”
Section: Valorisation Strategies Challenges and Trendsmentioning
confidence: 99%
“…Interestingly, some wild species are now re-emerging in gardens and kitchens of urban areas around Europe, being increasingly found in farmers' markets, gourmet food shops, and restaurants (Łuczaj et al, 2012;Tardío, 2005;Vasquezde, 2016). Nevertheless, WEPs lack recognition as significant contributors to the human diet in developed countries.…”
Section: Valorisation Strategies Challenges and Trendsmentioning
confidence: 99%